ANA-associated uveitis in the presence of reactivated HHV-7 infection in a patient with MBL deficiency (Ukrainian Journal of Ophthalmology, 2025)
Bilateral, ANA-positive uveitis developed in a patient with primary total mannose binding lectin (MBL) deficiency during human herpes virus type 7 (HHV-7)  reactivation from latently infected salivary glands. The diagnosis of uveitis was confirmed based on eye examination, findings of optical coherence tomography, and elevated serum antinuclear antibody titer (1:320). HHV-7 reactivation from persistence was verified by blood white cell polymerase chain reaction (PCR) and eye swab PCR. The patient was diagnosed with primary MBL deficiency based on the results of enzyme-linked immunosorbent assay and special genetic testing. The serum MBL level was zero, but all other studied characteristics were within respective reference ranges. We identified three pathologic polymorphisms (223 С/Т, 230 G/A, and 239 A/G) in the MBL-2 gene, which indicated a genetic origin for the detected immunodeficiency. The results of these tests provided a rationale for administering a comprehensive treatment for suppression of the autoimmune process (rituximab and methotrexate), elimination of HHV-7 DNA from blood white cells and ocular smears (valganciclovir) and compensation of primary immunodeficiency by replacement therapy with intravenous infusion of solvent-detergent-treated fresh frozen plasma containing MBL. Our comprehensive approach to treatment led not only to a complete remission of uveitis, but also to compensation of other autoimmune, allergic and infectious symptoms and signs of the immunodeficiency. The data from this report expand our knowledge on the heterogeneity of clinical signs and symptoms of primary MBL deficiency in humans and provide pathways to studies on new potential pathogenetic mechanisms of autoimmune lesions in this genetic immune dysfunction which is one of the most common in the population.
Keywords: uveitis; HHV-7; mannose binding lectin deficiency